(untitled) (Journal of history, 2019)
This article is the result of the study of some theoretical and methodological problems of the dissertation «The history of the formation of the ethnic territory of the Kazakh people (XV century-beginning of the XVIII century)». This is a fundamental and very topical issue of the national history of the Kazakh people. Therefore, our task in this article is to identify the main factors in the formation of ethnic territory among nomadic peoples, since nomadism is one of the most important phenomena that influenced the formation of the Kazakh people’s possessions. In this regard, the author examines such concepts as «ethnic territory», «economic and cultural type», «landscape», as a result of which an analysis of the study of the problem in the works of scientists was made. The study clarified the relationship of a number of factors, such as geographical location, climatic conditions, tribal organization, mode of production in the formation of the ethnic territory of the nomads. The conclusions are made about the patterns of formation of the ethnic territory of the nomadic Kazakh people.